Going West: Temporary immigration and the higher educational journey of Palestinian students from East to West Jerusalem - Diab, Al-Khansaa (Journal of International Students, 2026)
This qualitative study examined the daily educational experiences of Palestinian students from East Jerusalem who travel to universities in West Jerusalem. While existing research focuses on traditional international student mobility, limited attention has been given to students crossing internal boundaries within contested urban spaces. Through interviews with 27 Palestinian students selected from a larger research project and enrolled in Israeli universities, this research explored how students navigate daily border crossings for education within settler colonial structures. Three main themes emerged from the analysis: (1) Systemic barriers and daily struggles, where students experience checkpoint crossings and institutional discrimination as temporary immigration within their ancestral homeland; (2) cultural and linguistic navigation, where students develop strategic approaches for acquiring Hebrew and building cross-cultural relationships while preserving Palestinian identity; and (3) identity and educational resistance, where students view their education as collective Palestinian investment rather than individual assimilation. These findings reveal how daily border crossing creates unique forms of temporary immigration that challenge conventional frameworks of mobility. The research highlights what we call "settler colonial internal bordering": boundaries within indigenous territories that create immigration-like experiences for native populations accessing dominant institutions. Students' complex navigation strategies demonstrate how indigenous peoples can strategically engage with colonial educational systems while maintaining cultural sovereignty and political autonomy. This research contributes to understanding educational mobility in contested spaces and offers insights for academic institutions, policymakers, and indigenous communities navigating similar colonial structures globally